English Proficiency Test on Admission: Development, Implementation, Challenges and Future Directions - Hafizoah, Kassim; Fatimah, Ali; Nik Aloesnita, Nik Mohd Alwi; Norrihan, Sulan; Nor Suhardiliana, Sahar; Noor Raha, Mohd Radzuan; Suriya Kumar, Sinnadurai (UM Press, 2018)
Teaching and Learning English in Malaysian Higher Education contains a compilation of existing ELT practices from some Malaysian public universities concerning programme or course design, classroom practice and assessment practice. The volume sets out to emphasise the close links between curriculum, delivery and assessment. The different chapters reflect an agenda believed to be of significance to the different universities, which may at the same time be of interest and of practical use to English language teaching professionals in Malaysia and beyond.